2002
DOI: 10.1002/ffj.1112
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antimicrobial activity of the essential oil of Hypericum maculatum Crantz

Abstract: For the first time the composition of the essential oil of Hypericum maculatum Crantz has been determined by GC and GC-MS. The oil consisted of a large number of components in low percentages. Only five components exceeded a 5% level:ˇ-farnesene (10.0%), n-undecane (8.2%),ˇ-caryophyllene (7.6%), υ-cadinene (7.2%) and -muurolene (5.2%). The oil showed strong antimicrobiological activity against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella enteritidis, Klebsiella pneumoniae, Bacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 4 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…microcalycinum Chaix., H. Lysimachioides Boiss var. lysimachioides [49], H. Scabroides Robson & Poulter, H. triquetrifolium Turra [50], H. maculatum Crantz [51], H. perforatum L. [52], H. hirsutum L. [53] and H. cordatum Vell. [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…microcalycinum Chaix., H. Lysimachioides Boiss var. lysimachioides [49], H. Scabroides Robson & Poulter, H. triquetrifolium Turra [50], H. maculatum Crantz [51], H. perforatum L. [52], H. hirsutum L. [53] and H. cordatum Vell. [54].…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activity of H. triquetrifolium was previously reported only against Bacillus brevis , Bacillus cereus , Escherichia coli PBR 322 , Escherichia coli PUC 9 , Pseudomonas aeruginosa and Staphylococcus aureus [51]. However, the antimicrobial activity are generally influenced by the type of assay used [55].…”
Section: Discussionmentioning
confidence: 99%
“…Hypericum perforatum L. or St. John's wort (Clusiaceae) is a perennial rhizomatous herb traditionally used in herbal medicine throughout the world. Although various activities of H. perforatum extracts have been reported such as antibacterial, antiviral, wound healing, antioxidant, antimicrobial, anti-inflammatory, antinociceptive, antitumor, antiangiogenic, and immunomodulatory activity [1][2][3][4][5][6][7][8][9][10][11], the focus of interest is on its potential as an herbal antidepressant [2]. Flora Croatica Database (FCD) [12] describes two subspecies of H. perforatum in Croatia: ssp.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial activity results of H.adenotrichum root (0.156 mg/mL) essential oil against S. aureus is close to the standard compounds (Ampicillin and Clarithromycin). In a prior study, Gudzic et al reported that the essential oil from H. maculatum Crantz in Serbia exhibited a wide range of antibacterial effects (12-16 µL/mL), particularly against S.aureus, E. coli, P. aeruginosa, S. enteritidis, K. pneumoniae, and B. subtilis [36]. Kizil et al investigated the antimicrobial activity of the essential oils of H. scabrum L., H. scabroides, and H. triquetrifolium Turra against the test organisms and a yeast [37].…”
Section: Resultsmentioning
confidence: 99%